Sanctioning Pandemic-plagued Iran. Issue 3 (3rd May 2020) - Fitzpatrick, Mark
Abstract : The US is applying sanctions to Iran indiscriminately, contravening a moral and reputational imperative to ensure that American policies do not contribute to more COVID-19 deaths.